Keefektivan Komunikasi dalam Pengembangan Peran-Peran Kelembagaan Agropolitan - S. Oktarina; Sumardjo .; E. Rustiadi (Institut Pertanian Bogor, 2008)
The aim of this research was to find the farmers perception about the agropolitan institutional role performance, tomeasure the level of communication’s effectiveness and to find some factor that influence of its. The design andmethods in this research was survey and stratified random sampling. The data was obtained from three villages for120 respondents. Data was analyzed by non parametric statistic, in this case was Rank Spearman.The result shownthat farmer’s perception about agropolitan institutional role were central, province and regency team work,agricultural extension agents, bussiness agent, farmer team work, PH and STA institutional actually haven’t exactlyyet. The farmer perception is linierly, by using communicative method and rare frequency. The farmerscommunication in agropolitan institutional roles development haven’t effective yet. Some factors of respondentcharacteristic that correlate with the intensity of farmer’s social interaction, there are low education, experience andfarmer’s income. The role of central, province,regency team work, agricultural extension agents, and farmer teamwork correlate significantly with the intensity of farmer’s social interaction and the effectiveness of farmer’scommunication. The intensity of farmer’s social interaction correlate significantly with farmer’s perception andfarmer’s behavior.